PENENTUAN SKALA PRIORITAS DAN POLA PENANGANAN KERUSAKAN JALAN LINGKUNGAN KAWASAN PERMUKIMAN KUMUH DI KOTA MATARAM - TEGUH PRIYANTO; I DEWA MADE ALIT KARYAWAN; MADE MAHENDRA (GANEC SWARA, 2023)
Population growth, economy and urbanization are several factors causing the creation of slum areas in urban areas. One indicator of a slum area is the poor quality of the road surface. This condition becomes a negative paradigm towards the implementation of development by the Government. Weak databases lead to not optimal programming and planning processes that lead to not optimal implementation and supervision in the field. This study aims to compile a database for environmental road handling plans in slum settlement areas based on Geographic Information Systems (GIS), so as to provide information on priority scales and patterns of environmental road management in slum settlement areas. The method used is descriptive quantitative by weighting based on 3 parameters, namely: 1) road management program, 2) the number of dwellings/houses that have direct access to the road and, 3) other considerations including strategic location value, population, and condition socioeconomic. This research concludes that the programming and planning process which is carried out subjectively based on conditions and needs in the field can make efficient use of the budget so that it is right on target in the following years. So that it can be used as a recommendation for determining priorities on each environmental road segment and a program for handling patterns of slum area scale in the city of Mataram